The effect of a Mindfulness-based stress reduction program on the mental health of a sample of Italian healthcare professionals: A quasi-experimental study design - Martina FINISTRELLA; Elisa LUCHINA (GIornale Italiano di Psicologia e Medicina del Lavoro)
Introduction: Healthcare workers (HCWs) are commonly exposed to work-related stress, potentially leading to burnout syndrome. Mindfulness-based stress reduction (MBSR) is recognized for its potential to alleviate distress, reduce emotional exhaustion, and enhance attention to the present moment. This study evaluates the effectiveness of MBSR in improving stress management and emotional regulation among healthcare workers. Methods: This study involved 43 hospital employees from Milan, who participated in a structured 8-week Mindfulness-Based Stress Reduction (MBSR) program. Each session lasted 2 hours per week. At the beginning of the study, we collected socio-demographic data along with baseline responses to the following comprehensive questionnaires: the Mindful Attention Awareness Scale (MAAS), the Maslach Burnout Inventory (MBI), the Perceived Stress Scale (PSS-10), the Interpersonal Reactivity Index (IERQ), the Emotion Regulation Questionnaire (ERQ), and the Difficulties in Emotion Regulation Scale (DERS). Post-intervention assessments were completed by 28 of the participants. Results: The participant demographic included 37.2% nurses, 27.9% doctors, and 34.9% other health professions. Notable improvements were observed in the Mindful Attention Awareness Scale (MAAS) scores, which increased by 8.37 (p = 0.027), and the Perceived Stress Scale (PSS-10) scores, which decreased by 4.55 (p = 0.011) post-intervention. Changes were less significant in the Interpersonal Reactivity Index (IERQ) with an increase of 0.69 (p = 0.553), the Maslach Burnout Inventory (MBI) with a marginal improvement of 0.11 (p = 0.788), the Difficulties in Emotion Regulation Scale (DERS) with a decrease of 1.67 (p = 0.533), and the Emotion Regulation Questionnaire (ERQ) with a decrease of 1.26 (p = 0.712) scores. Discussion and Conclusion: The findings confirm the effectiveness of the MBSR program in significantly improving mindfulness and reducing stress among healthcare professionals. However, changes in emotional regulation and burnout were less pronounced, suggesting the need for further research in these areas.